DETEKSI DINI, PENENTUAN GRADING DAN MANAJEMEN MULTIDISIPLIN ORAL SQUAMOUS CELL CARCINOMA (OSCC) - Sitompul, Daniel Rexi; Mutiara Pangaribuan; Albertus Samosir (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2024)
Oral squamous cell carcinoma (OSCC) is the most common type of oral cancer with high morbidity and mortality rates. This study aims to examine a comprehensive approach to the early detection, grading and multidisciplinary management of OSCC. Early detection of OSCC, through the use of clinical examination, radiologic imaging and molecular biomarkers, is essential to improve patient prognosis. Grading of OSCC using histopathological evaluation and the TNM classification system, provides critical information on tumor aggressiveness and guidance for therapeutic decisions. Effective management of OSCC requires a multidisciplinary approach involving various medical specialties to provide comprehensive care. Primary therapies such as surgery, radiation therapy, and chemotherapy, as well as adjuvant therapies including immunotherapy and targeted therapies, play an important role in optimizing clinical outcomes and patient quality of life. The study also identifies recent advances in imaging technology and genetic analysis that can improve diagnostic accuracy and treatment effectiveness. Keyword : Oral squamous cell carcinoma, multidiscipline, quality of life